1997
DOI: 10.1212/wnl.48.5.1266
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of full‐length mRNA for c BCD541 does not correlate with spinal muscular atrophy phenotype severity

Abstract: Spinal muscular atrophy (SMA) is characterized by degeneration of spinal cord anterior horn cells and muscular atrophy and has three phenotypes based on clinical severity and age of onset. One of the responsible genes for SMA is the survival motor neuron (SMN) gene, which is homozygously absent or interrupted in more than 90% of SMA patients. The cBCD541 (BCD) gene is a highly homologous copy of the SMN gene, which has a single synonymous transition in the coding region and may compensate for the loss of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…It has been shown in studies using lymphocytes and lymphoblastoid cells from SMA patients that there is no significant difference in the amount of full-length mRNA species among patients with type I-II and III SMA [20,41]. Gavrilov et al [20] have observed that the ratio of the truncated mRNA species to full-length mRNA species was significantly higher in type I-II than in type III SMA, and that type I-II patients appeared to produce significantly more truncated mRNA species than type III patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in studies using lymphocytes and lymphoblastoid cells from SMA patients that there is no significant difference in the amount of full-length mRNA species among patients with type I-II and III SMA [20,41]. Gavrilov et al [20] have observed that the ratio of the truncated mRNA species to full-length mRNA species was significantly higher in type I-II than in type III SMA, and that type I-II patients appeared to produce significantly more truncated mRNA species than type III patients.…”
Section: Discussionmentioning
confidence: 99%
“…s Messenger RNA analysis Total RNA was extracted from leukocytes using the acid guanidium thiocyanate-phenol-chloroform method, and SMN1 or SMN2 mRNA species were amplified by reverse transcriptase (RT)-PCR according to the method described previously [41]. The primer ex1-F (5'-GCT ATG GCG ATG AGC A GC GGC-3') was newly designed based on the sequences of exon 1.…”
Section: Patients and Methods S Patientsmentioning
confidence: 99%
“…The signal intensity of the bands on the gel was measured by a charge-coupled device imaging system, the Densitograph AE-6900-F (Atto, Tokyo, Japan) [15]. For each carrier, the peak intensity ratio between two alleles using undigested PCR products was calculated and used as a correction factor.…”
Section: S Pcr Amplification Of the Ar Genementioning
confidence: 99%
“…SMN2 is identical in amino acid composition to SMN1 and remains intact in SMA patients 4 . As both genes produce SMN protein 8,9 , an increase in SMN2 copy number could raise SMN protein levels and result in a milder phenotype; however, efforts to demonstrate a correlation between SMN2 copy number and disease severity have produced conflicting results [19][20][21][22] . NAIP, a gene that lies 16.5 kb downstream of SMN, has also been suggested to be an SMA modifier due to its proximity to SMN and its homology to apoptosis inhibitory proteins 23 , but nearly one-third of type I SMA patients fail to show deletions or mutations of NAIP (refs 19,23).…”
mentioning
confidence: 99%